From A Semi-Federal to An Administrative-Technocratic Model: The Paradigm Shift in Decentralization in Contemporary Indonesia - Jati, Wasisto Raharjo (UI Scholars Hub, 2024)
The implementation of decentralization policies in Indonesia highlights contested interests between central and subnational governments. Particularly since the end of authoritarian rule, decentralization efforts have continuously faced tensions with recentralization interests. These interests do not necessarily aim to restore a strong state with a hierarchical command structure. Instead, the recent decentralization policies tend to display an administrative state supported by hierarchical policies. Consequently, the autonomous regions are no longer fully autonomous in managing their internal affairs but are increasingly required to comply with national policies. This study seeks to further investigate the reasons behind these shifts through a critical discourse analysis of relevant documents, FGDs, and expert interviews. Primary data were collected from in-depth interviews and FGD recordings, while secondary data were obtained from relevant literature. These data were then analyzed by synthesizing key findings per each expert and applying a link-and-match approach. This study seeks to validate the collected information to facilitate the interpretation of new findings, which were then presented in a draft outlining the debates on the topic and the position of the study. The findings indicate that the paradigm shift has made decentralization more administratively burdensome for the subnational level, as demonstrated by the increased policy assistance from the central government. The central government manages decentralization at the provincial, district, municipal, and even village levels through targeted policy objectives with key indicators. Consequently, the current decentralization creates a dependent relationship between subnational governments and the central government, primarily through fiscal transfers. A limitation of this study includes the relatively unexplored responses from local officials.